Analisis Pengaruh Sektor Pertanian Terhadap Perekonomian di Provinsi Medan - Elsa Dameria Naibaho; Darwin Damanik (Jurnal Akuntan Publik, 2023)
This study aims to analyze the influence of the agricultural sector on the economy in Medan Province. The agricultural sector plays a vital role in the economy of a region, particularly in agrarian areas like Medan Province. The data used in this study are secondary data obtained from relevant institutions and statistical agencies. The research method employed is linear regression analysis, using the dependent variable of economic growth in Medan Province and the independent variable of agricultural sector production value. The results of the analysis indicate a positive relationship between the agricultural sector and economic growth in Medan Province. The regression results show that the production value of the agricultural sector contributes significantly to economic growth in the region. This indicates that the development of the agricultural sector has a positive impact on the economy of Medan Province. The study also identifies other factors that can influence the relationship between the agricultural sector and the economy, such as climate factors, government policies, and market factors. The findings of this research can serve as a basis for relevant stakeholders, both the government and industry players, in formulating policies and development strategies for the agricultural sector to enhance economic growth in Medan Province.